2022-RA-820-ESGO The role of minimally invasive secondary cytoreduction in recurrent ovarian cancer patients. (20th October 2022) - Conte, Carmine; Marchetti, Claudia; Loverro, Matteo; Giudice, Maria Teresa; Rosati, Andrea; Gallotta, Valerio; Scambia, Giovanni; Fagotti, Anna
Abstract : Introduction/Background: Retrospective series have shown minimally invasive secondary cytoreductive surgery (MI-SCS) is a feasible approach in selected cases of recurrent ovarian cancer (ROC). However, no predictors of MI-SCS feasibility are currently available. This study aims to identify predictive factors of MI-SCS feasibility and to compare perioperative and survival outcomes in a matched series of ROC patients who underwent secondary cytoreduction via an open or minimally invasive surgical approach. Methodology: We retrospectively identified all platinum-sensitive epithelial ROC patients who underwent minimally invasive or laparotomic (LPT) SCS between January 2013 and July 2020. All patients underwent preoperative positron emission tomography computed tomography (PET-CT) scan and diagnostic laparoscopy before SCS. A 1:2 propensity score-matched analysis was performed to balance predictive factors of MI-SCS. Results: Overall, 276 cases were identified (62 MI-SCS and 214 LPT), and a complete gross resection (CGR) was achieved in 262 (94.9%) patients. At multivariate analysis, predictive factors for MI-SCS were NACT (p=0.007), site of recurrence (p=0.031), and number of lesions (p=0.001) (Table).In the propensity-matched population (39 MI-SCS and 78 LPT), CGR was similar for both groups (39 MI-SCS vs 72 LPT; p=0.082). Early post-operative complications were significantly higher in the LPT-SCS (33.3%) than in the MI-SCS (10.3%) group (p=0.004). Only one (2.6%) patient experienced a grade≥3 early post-operative complication in the MI-SCS compared to 13 (16.7%) patients in the LPT cohort (p<0.001).The median follow-up period was 32 months (range18–92) in the propensity-matched population.The median post-recurrence survival (PRS) was 81 months in the MI-SCS group and not reached in the LPT Group (p=0.111). Conclusion: Patients with single or oligometastatic recurrences can be offered MI-SCS, mainly if localized in the lymph-nodes and/or if they received NACT at primary diagnosis. MI-SCS is associated with favourable perioperative outcomes with no statistically significant differences in terms of PRS with respect to open approach.